Recent Advances in Solid Tumor CAR-T Cell Therapy: Driving Tumor Cells From Hero to Zero? - Safarzadeh Kozani, Pouya; Safarzadeh Kozani, Pooria; Ahmadi Najafabadi, Milad; Yousefi, Fatemeh; Mirarefin, Seyed Mohamad Javad; Rahbarizadeh, Fatemeh (Frontiers in Immunology, 2022)
Chimeric antigen receptor T-cells (CAR-Ts) are known as revolutionary living drugs that have turned the tables of conventional cancer treatments in certain hematologic malignancies such as B-cell acute lymphoblastic leukemia (B-ALL) and diffuse large B-cell lymphoma (DLBCL) by achieving US Food and Drug Administration (FDA) approval based on their successful clinical outcomes. However, this type of therapy has not seen the light of victory in the fight against solid tumors because of various restricting caveats including heterogeneous tumor antigen expression and the immunosuppressive tumor microenvironments (TME) that negatively affect the tumor-site accessibility, infiltration, stimulation, activation, and persistence of CAR-Ts. In this review, we explore strategic twists including boosting vaccines and non-cross-reactive designing implementations that can support CAR-T expansion, proliferation, and tumoricidal capacity. We also step further by underscoring novel strategies for triggering endogenous antitumor responses and overcoming the limitation of poor CAR-T tumor-tissue infiltration and the lack of definitive tumor-specific antigens. Ultimately, we highlight how these approaches can address the mentioned arduous hurdles.